(untitled) (REMUNOM, 2026)
Temporomandibular disorder (TMD) comprises a set of conditions affecting the temporomandibular joint, masticatory muscles, and associated structures; it is a public health problem due to its prevalence and negative impact on quality of life. Primary Health Care serves as the main gateway to the Unified Health System (SUS), and dental surgeons working at this level play a fundamental role in the identification and management of these patients. This is an observational descriptive study conducted with dental surgeons working in Primary Health Care (PHC) in the city of Teresina, Piauí. Data collection was performed using a semi-structured questionnaire, administered both remotely and in person, covering sociodemographic characteristics, professional background, and subject-specific topics. Data were subjected to descriptive statistical analysis. A total of 62 dental surgeons participated, mostly female, with over 10 years of professional experience and graduates of public universities. Self-assessment of knowledge regarding TMD was predominantly rated as fair, although most participants claimed to recognize patients with this condition. The findings highlight gaps in theoretical and practical knowledge regarding TMD, consistent with the literature, which points to limitations in academic training and continuing education on the subject. It is concluded that these Primary Health Care professionals possess intermediate knowledge of temporomandibular disorders, which may negatively impact the clinical management of these patients.